In situ Dynamics of O2, pH, Light, and Photosynthesis in Ikaite Tufa Columns (Ikka Fjord, Greenland)—A Unique Microbial Habitat - Trampe, Erik C. L.; Larsen, Jens E. N.; Glaring, Mikkel A.; Stougaard, Peter; Kühl, Michael (Frontiers in Microbiology, 2016)
The Ikka Fjord (SW Greenland) harbors a unique microbial habitat in the form of several hundred submarine tufa columns composed of ikaite, a special hexahydrate form of calcium carbonate that precipitates when alkaline phosphate- and carbonate-enriched spring water seeping out of the sea floor meets cold seawater. While several unique heterotrophic microbes have been isolated from the tufa columns, the microbial activity and the boundary conditions for microbial growth in ikaite have remained unexplored. We present the first detailed in situ characterization of the physico-chemical microenvironment and activity of oxygenic phototrophs thriving within the ikaite columns. In situ underwater microsensor measurements of pH, temperature, and irradiance in the porous ikaite crystal matrix, revealed an extreme microenvironment characterized by low temperatures, strong light attenuation, and gradients of pH changing from pH 9 at the outer column surface to above pH 10 over the first 1-2 cm of the ikaite. This outer layer of the freshly deposited ikaite matrix contained densely pigmented yellow and green zones harboring a diverse phototrophic community dominated by diatoms and cyanobacteria, respectively, as shown by amplicon sequencing. In situ O2 measurements, as well as underwater variable chlorophyll fluorescence measurements of photosynthetic activity, demonstrated high levels of oxygenic photosynthesis in this extreme gradient environment with strong irradiance-driven O2 dynamics ranging from anoxia to hyperoxic conditions in the ikaite matrix, albeit the local formation of gas bubbles buffered the day-night dynamics of O2 in the tufa columns. The microbial phototrophs in the ikaite matrix are embedded in exopolymers forming endolithic biofilms that may interact with mineral formation and cementing of ikaite crystals.